The development of an ARM-based OBC for a nanosatellite - Brand, Christiaan Johannes Petrus (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2007.